2017
DOI: 10.2169/internalmedicine.56.7501
|View full text |Cite
|
Sign up to set email alerts
|

Euglycemic Diabetic Ketoacidosis with Persistent Diuresis Treated with Canagliflozin

Abstract: Diabetic ketoacidosis is characterized by hyperglycemia, anion-gap acidosis, and increased plasma ketones. After the resolution of hyperglycemia, persistent diuresis is rare. We herein report the case of a 27-year-old Asian woman with type 2 diabetes who was treated with a sodium-glucose cotransporter 2 (SGLT2) inhibitor (canagliflozin) who developed euglycemic diabetic ketoacidosis and persistent diuresis in the absence of hyperglycemia. Physicians should consider euglycemic diabetic ketoacidosis in the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…SGLT2i‐associated DKA is often deemed “euglycaemic,” but it should be noted that only approximately one third of patients were admitted with a glucose level of less than 200 mg/dL. Nonetheless, the average glucose levels reported in SGLT2i‐associated DKA were lower than those in the rare cases of DKA reported in T2D patients (613.8 ± 114.5 mg/dL), probably because drug‐induced glycosuria keeps glucose levels low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGLT2i‐associated DKA is often deemed “euglycaemic,” but it should be noted that only approximately one third of patients were admitted with a glucose level of less than 200 mg/dL. Nonetheless, the average glucose levels reported in SGLT2i‐associated DKA were lower than those in the rare cases of DKA reported in T2D patients (613.8 ± 114.5 mg/dL), probably because drug‐induced glycosuria keeps glucose levels low.…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved a total of 105 episodes of DKA in patients receiving SGLT2i from May 2014 to April 2017 . Demographic characteristics, type of diabetes and type of SGLT2i are reported in Table .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In a review of literature, 46 cases of diabetic ketoacidosis associated with the use of SGLT-2 were found and, in 70% of the cases, the ketoacidosis was euglycemic [ 23 ]. The main mechanism of action is the inhibition of glucose uptake in proximal tubules, increasing glycosuria [ 24 ]. In addition, SGLT-2 inhibitors significantly increase plasma glucagon levels through a decrease in paracrine inhibition of insulin and possibly due to the inhibition of glucose transport into pancreatic α cells by SGLT-2 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SGLT-2 inhibitors significantly increase plasma glucagon levels through a decrease in paracrine inhibition of insulin and possibly due to the inhibition of glucose transport into pancreatic α cells by SGLT-2 [ 22 ]. At the same time, they decrease 3-hydroxybutyrate and acetoacetate elimination at the kidney level [ 24 28 ]. Moreover, when blood glucose levels decrease, patients that are being treated with insulin decrease its administration.…”
Section: Discussionmentioning
confidence: 99%
“…According to this case report there is still ongoing polyuria even after the patient has had euglycemia. 6 In another previous study shown that, polyuria was continued even after 11 days of discontinuation of SGLT-2 inhibitors. 10 In our case on the 7 th day of treatment, the serum glucose measurement was 96 mg/dL, the-refore the urine measurement showed +++ glycosuria.…”
Section: Discussionmentioning
confidence: 94%